Preparation and characterization of polyhydroxybutyrate/ polycaprolactone/ stearate magnesium-aluminium layered double hydroxide nanocomposites - Liau, Cha Ping (2013)
Disposal of non-biodegradable polymer waste leads to environmental problems which produce highly toxic to living organisms. Therefore, production of biodegradable polymer is necessary to resolve environmental problems and to obtain materials with excellent properties for other uses. The anionic clay Mg-Al layered double hydroxide (Mg-Al LDH) nanofiller with Mg2+:Al3+ (3:1) ratio was synthesized by co-precipitation method from nitrate salt solution at pH 9. Stearate Mg-Al LDH nanofiller was prepared by anion exchange method where the nitrate anions replace by stearate anions between the LDH interlayer. This chemical modification leads to expand the interlayer d-spacing of LDH and easier for the polymer chain intercalated into the LDH interlayer. Polyhydroxybutyrate (PHB)/polycaprolactone (PCL) polymer blends and PHB/PCL/stearate Mg-Al layered double hydroxide (stearate Mg-Al LDH) polymer nanocomposites with distinct contents were prepared via a solution casting intercalation method to avoid thermal instability of pure PHB. Blend of both biodegradable polymer to achieve unique properties and the additional of stearate Mg-Al LDH nanofiller is to improve the compatibility between the filler and polymer matrix. The characteristics of prepared samples were investigated in term of spectroscopic, thermal, mechanical and morphology. Fourier Transform Infrared Analysis (FTIR) spectra shows stearate anions are successfully replaced the nitrate anion due to the presence of carboxylic acid (COOH) functional group. Moreover, the formation of polymer nanocomposites only involves physical interaction as there are no new functional groups or new bonding present. In addition, XRD results shows increasing interlayer d-spacing from 8.66 Å to 32.97 Å in stearate Mg-Al LDH nanofiller due to the intercalation of long chain hydrophobic tail stearate anions into the LDH interlayer. TEM results revealed that additional of 1.0 wt % stearate Mg-Al LDH nanofiller shows a homogeneous dispersion in the 80PHB/20PCL polymer blend matrix. Thus, higher miscibility and strong interaction between filler and polymer matrix lead to the higher thermal stability in TGA characterization. The presence of 1.0 wt % of the stearate Mg-Al LDH nanofiller improved drastically in elongation at break (around 300 %) and tensile strength (around 66 %) when compare with PHB/PCL polymer blends. Besides, investigation of scanning electron microscopy (SEM) shows fracture surface of polymer nanocomposites are less porosity, homogeneous dispersed and well stretched before it breaks. This suggests that filler act as compatibilizer to improve the mixing between filler and polymer matrix. As a conclusion, 80PHB/20PCL/1stearate Mg-Al LDH polymer nanocomposite as an optimum ratio between filler and polymer matrix due to the enhancement drastically in properties when compare with those pure PHB, pure PCL and PHB/PCL polymer blends.